Cross-Border Shadow Education: Private Supplementary Tutoring in the Global Education Industry - Bray, Marc; Zhang, Wei (Revista Española de Educación Comparada, 2022)
This paper focuses on the so-called shadow education provision of private supplementary tutoring by companies operating internationally. Some have a history of decades, while others are younger and emerged to take advantage of technological developments. Contributing to analysis of the Global Education Industry, the paper notes variations in the penetration and manifestation across world regions. In so doing, it draws on theories of isomorphism, while noting divergence as well as convergence in institutional models. The analysis includes remarks on regulatory regimes, many of which permit and even facilitate such international companies, but some of which – most obviously in China – restrict their operation. Thus, conceptually the paper analyses patterns with understanding of the forces in operation. Some of these forces are economic (pricing, marketing, etc.), but others are political (shaped particularly by government regulations), and social (shaped by different socio-economic groups within the countries in question).